1981
DOI: 10.1073/pnas.78.9.5310
|View full text |Cite
|
Sign up to set email alerts
|

Three tRNA binding sites on Escherichia coli ribosomes.

Abstract: The binding of N-acetyl-Phe-tRNArhe (an analogue of peptidyl-tRNA), Phe-tRNAPhe, and deacylated tRNAPhe to poly(U)-programmed tightly coupled 70S ribosomes was studied. The N-acetyl-Phe-tRNAPhe binding is governed by an exclusion principle: not more than one N-acetyl-Phe-tRNA hC can be bound per ribosome, although this peptidyl-tRNA analogue. can be present either at the aminoacyl-tRNA (A) site or the peptidyltRNA (P) site. Two Phe-tRNArhe molecules are accepted.by one ribosome in the presence of poly(U). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
132
2
11

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 16 publications
12
132
2
11
Order By: Relevance
“…For instance, while four tRNA-binding sites are proposed, only two or three are occupied at any one time. This agrees with the data of Rheinberger et al (1981) who found 2-2.5 tRNAs bound during translation. It also includes the R and D sites, which increase the fidelity of translation (Lake, 1981;Nierhaus et al, 1980).…”
Section: Proofreading and Trna Bindingsupporting
confidence: 93%
See 2 more Smart Citations
“…For instance, while four tRNA-binding sites are proposed, only two or three are occupied at any one time. This agrees with the data of Rheinberger et al (1981) who found 2-2.5 tRNAs bound during translation. It also includes the R and D sites, which increase the fidelity of translation (Lake, 1981;Nierhaus et al, 1980).…”
Section: Proofreading and Trna Bindingsupporting
confidence: 93%
“…The A and P sites are as usually proposed. The D (discharge) site corresponds to the E site of Rheinberger et al (1981). The name has been changed for acronymic reasons.…”
Section: Proofreading and Trna Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer RNAs (tRNAs) are the substrates used by ribosomes for synthesizing proteins+ To understand the mechanism of translation at the molecular level, it is essential to understand how tRNAs interact with the ribosome (Rheinberger et al+, 1981;Grajevskaja et al+, 1982;Kirillov et al+, 1983;Lill et al+, 1984)+ The anticodon arm of P-site tRNA interacts with mRNA in the vicinity of the cleft formed by the platform and the head of the 30S subunit (Lake, 1980;Gornicki et al+, 1984)+ The acceptor arms of A-site and P-site tRNAs interact with the peptidyl transferase center, which lies close to the base of the central protuberance of the 50S subunit (Ofengand, 1980;Olson et al+, 1982;Wower et al+, 1989)+ During peptide bond formation, the CCA-39 termini of A-site and P-site tRNAs must be proximal to allow peptidyl transfer, while their anticodons interact with adjacent codons on mRNA (Fairclough & Cantor, 1979a;Matzke et al+, 1980)+ Several models have been proposed for the arrangement of A-site and P-site tRNAs in the ribosome based on stereochemical considerations (Fuller & Hodgson, 1967;Woese, 1970;Rich, 1974;Sundaralingam et al+, 1975;Lake, 1977;Spirin & Lim, 1986;McDonald & Rein, 1987;Prabahakaran & Harvey, 1989;Nagano et al+, 1991;Easterwood et al+, 1994), fluorescence resonance energy transfer (FRET) (Johnson et al+, 1982;Paulsen et al+, 1983), crosslinking studies (Ofengand, 1980, Ofengand et al+, 1981Wower et al+, 1989Wower et al+, ,hotra et al+, 1998, and other methods (Spirin, 1983;Smith & Yarus, 1989;Wagenknecht et al+, 1989;Nierhaus et al+, 1998)+ Most of these models can be assigned to either the R (Rich, 1974) or S (Sundaralingam et al+, 1975) orientations+ In the R orientation, the T loop of A-site tRNA ...…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the ionic strength Maximal stimulation of the binding of tuberactinomycin to programmed ribosomes was achieved by the addition of a two-molar excess of tRNAPhe (375 pmol tRNAPhe, see table 1). At this molar ratio tRNAPhe binds exclusively to the ribosomal P-site [13]. The addition of more tRNA does not further increase the drug binding (table 1, cf.…”
Section: Resultsmentioning
confidence: 90%